Role of stromal CD10 expression in classifying phyllodes tumors - Manoharan, Hemavathi; Manoharan, Kavitha; Rajagopalan, Padmavathi (International Journal of Research in Medical Sciences, 2019)
Background: Phyllodes tumor is a rare fibroepithelial tumor of the breast comprising less than 1% of all primary breast tumor. Phyllodes tumors are classified into benign, borderline and malignant based on histological criteria. Grading of phyllodes tumor is important as it determines the biological behaviour of the tumor. The aim of the present study was to identify the incidence, pathological features of benign, borderline and malignant phyllodes tumors and to compare the CD10 expression in benign, borderline and malignant phyllodes, in order to highlight its diagnostic significance. Methods: This is a retrospective study conducted in Department of Pathology, Madras Medical College, Chennai for a period of 3 years. The clinical and pathological findings of phyllodes tumors were retrieved from the surgical pathology records. Totally 50 case were selected randomly (38 benign, 6 borderline and 6 malignant) and their representative formalin fixed paraffin embedded tissue samples were subjected to immunohistochemistry for CD10 expression. Results: In the 38 cases of benign phyllodes tumors, only three cases (7.9%) were CD10 positive. Three out of six cases (50%) of borderline phyllodes tumors showed CD10 positivity, whereas five out of six cases (83.3%) of malignant phyllodes tumor showed CD10 positivity. Conclusions: CD10 expression correlated well with grade of phyllodes tumors, which is of statistical significance and therefore it can be used in the determination of tumor grade and this may pave way for development of targeted therapies.